Potensi Aktivitas Antibakteri Minuman Fungsional Kombucha Berbahan Dasar Bunga Kecombrang (Etlingera elatior) Berdasarkan Lamanya Waktu Fermentasi - Putu Rima Sintyadewi; Pande P Elza Fitriani; Ida Ayu Putu Ary Widnyani; Putu Indrayoni (Jurnal Biologi Tropis, 2023)
According to same reports, kombucha is a functional beverage that has the ability to boost immune system function by increasing T cells and containing antimicrobial substances that guard against microbial illness. The antibacterial properties of kombucha derived from kecombrang flowers have not been examined in a any of the numerous studies conducted on the beverage’s antimicrobial activity. The purpose of this study is to investigate how the lengt of fermentation effects the kecombrang flower kombucha antibacterial effectiveness. Fermentation times for the treatments were as follows (P1) 0 days, (P2) 3 days, (P3) 6 days, and (P4) 9 days. The commensal pathogenic microorganisms Escherichia coli, Salmonella typhimurium and Stapylococcus aureus were employed in this study. According to the research findings, the antibacterial activity of kecombrang flower kombucha was significantly impacted (P<0,01) by the duration of fermentation. The maximun antibacterial activity was found in kecombrang flower kombucha that was fermented for nine days (P4). It had an inhibitory power of 12,0 mm against Escherichia coli, 11,5 mm against Salmonella typhimurium, and 14,5 mm against Staphylococcus aureus. Kecombrang flower kombucha is known for its broad spectrum of antibacterial activity, which can suppress the growth of both gram-positif and gram-negatif pathogenic bateria. Based on these results, kecombrang flower kombucha has the potential to be an antibacterial agent and can functions as an alternative approach to functional drinks to control commensal pathogenic bacteria.